The Arc of Faith-Based Initiatives Religion's Changing Role in Welfare Service Provision - Bartkowski, John P. (Springer International Publishing, 2018)
This volume offers an in-depth examination of a diverse range of faith-based programs implemented in three different geographical locales: family support in rural Mississippi, transitional housing in Michigan, and addiction recovery in the Pacific Northwest (Washington-Oregon). Various types of religious service providers-faith-intensive and faith-related-are carefully examined, and secular organizations also serve as an illuminating point of comparison. Among other insights, this book reveals how the "three C's" of social service provision-programmatic content, organizational culture, and ecological context-all combine to shape the delivery of welfare services in the nonprofit world. This book warns against simplistic generalizations about faith-based organizations. Faith-based providers exhibit considerable diversity and, quite often, remarkable resilience in the face of challenging social circumstances. An appreciation of these nuances is critical as policies concerning faith-based organizations continue to evolve.